Determining Factors of Student Learning Achievement - Hasan Basri (PINISI Discretion Review, 2022)
The COVID-19 pandemic has had an impact on various aspects. One of them is the education sector. The pandemic condition has consequences for changing the lecture system, from conventional to all-digital, so it is very important to assess student achievement. This study aims to determine the learning achievement in students of the Study Program of Sharia Economic Law STAIN Majene. This study uses a quantitative approach. The population in the study were all students of the Study Program of Sharia Economic Law STAIN Majene, amounting to 531 people. Sampling was done using a sample size calculator, and the number of samples was 224 people. The research instrument used an online questionnaire which was distributed to students and then documented. The data were then analyzed using ordinal regression test with t test to see the determinants of student achievement. The results showed that the factors that have an influence on student achievement are aspects of the way parents educate their children, aspects of interests and talents and aspects of discipline. While the psychological aspect has no influence on student achievement. Through this research, it is suggested that parents can continue to be involved in the development of a child and carry out their functions as parents. Likewise, the campus should continue to provide supervision, guidance and motivation to students so that students can maintain their discipline and interest in learning so that their learning performance will also continue to increase.